PERAN PROGRAM ROJHEK CINGUR RADIO NADA FM DALAM MELESTARIKAN BUDAYA LOKAL DI SUMENEP MADURA - Zein, Khoiruz; Indra Dewi, Sulih (Unitri Press, 2019)
The Rojhek Cingur program was one of the Nada FM radio broadcast programs produced and broadcasted for the first time in 2016. The program discussed the values ??and local culture of Madura delivered by the people, which was then combined with the news of cultural issues developing across the people. This research used descriptive qualitative type. The main informant of the study were the broadcaster of the Rojhek Cingur program and the Nada FM radio station manager. The data collection technique of this research was carried out by interview, documentation and observation. While the data analysis technique consisted of data collection, data reduction and data presentation. The data validation used data triangulation. The result showed that the Rojhek Cingur program was one of the Nada FM radio programs discussed cultural values. The role of Rojhek Cingur Nada FM radio program were (1) Rojhek Cingur was a rehabilitation of Madura culture, (2) Rojhek Cingur was an education and cultural socialization, and (3) Rojhek Cingur was an unifying media. The pattern of communication between broadcaster and Rojhek Cingur program listeners were (1) Two-way communication patterns (two way traffic communicatios), and (2) Multi-directional communication patterns.   Keywords: Mass Communication, Rujak Cingur program, Local Culture.